Studi Kuantitatif Pengaruh Kualitas Produk, Harga, dan Kualitas Pelayanan terhadap Kepuasan Konsumen Warmindokuy - Sari, Sri Rahayu Puspita; Yatun, Ratih Fitri (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2025)
The increasingly competitive culinary business landscape demands that business actors understand the factors influencing customer satisfaction in order to maintain loyalty and enhance competitiveness. Warmindokuy Bekasi, a popular dining destination among young people, faces the challenge of maintaining and increasing customer satisfaction. Customer satisfaction is influenced by various aspects, including product quality, price, and service quality. This study aims to determine the effect of product quality, price, and service quality on customer satisfaction at Warmindokuy Bekasi. This research is quantitative with a descriptive approach. Primary data was collected through a 20-item questionnaire distributed to 100 respondents. Data analysis was performed using IBM SPSS Statistics version 27, using a series of statistical tests, including validity, reliability, classical assumption tests, multiple linear regression, coefficient of determination (R²), F-test, and t-test. The results of the study indicate that partially, product quality significantly influences customer satisfaction, price significantly influences customer satisfaction, and service quality does not significantly influence customer satisfaction. However, simultaneously, all three variables—product quality, price, and service quality—have a positive effect on customer satisfaction at Warmindokuy Bekasi. This finding provides important implications for Warmindokuy management in formulating strategies to improve service and product quality to increase customer satisfaction and loyalty.